2019
DOI: 10.1021/acs.jpcc.9b02168
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5-Triazine-Based Pt(II) Metallogel Material: Synthesis, Photophysical Properties, and Optical Power-Limiting Performance

Abstract: A new Pt­(II) acetylide metallogel material (Pt-1) with 1,3,5-triazine core and 3,4,5-tris­(dodecyloxy)­benzamide terminal units was synthesized and characterized. Its photophysical properties were studied by UV–vis absorption, emission, transient absorption, Z-scan, and nonlinear transmission spectroscopy/technique. Pt-1 exhibits ligand-centered n−π* and 1π–π* transitions in the UV region, and broad, strong absorption bands mixed with intraligand charge transfer (1ILCT)/ligand-to-ligand charge transfer (1LLCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…To minimize their impact on sensitive human eyes and optical devices, optical‐limiting (OL) materials with high transmission and decreasing transmission of progressively increasing light intensities have received considerable attention [3] . Typical OL materials contain carbon‐based materials (including carbon black, carbon nanotubes, fullerenes and graphene), [4] organic dyes and polymers (such as phthalocyanine and porphyrin), [5, 6] inorganic metal nanoparticle and quantum dots, [7–9] as well as organic and inorganic hybrid materials [10–16] . Hybrid materials possessing flexibility and possible synergic effects of diverse components are promising OL materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize their impact on sensitive human eyes and optical devices, optical‐limiting (OL) materials with high transmission and decreasing transmission of progressively increasing light intensities have received considerable attention [3] . Typical OL materials contain carbon‐based materials (including carbon black, carbon nanotubes, fullerenes and graphene), [4] organic dyes and polymers (such as phthalocyanine and porphyrin), [5, 6] inorganic metal nanoparticle and quantum dots, [7–9] as well as organic and inorganic hybrid materials [10–16] . Hybrid materials possessing flexibility and possible synergic effects of diverse components are promising OL materials.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Typical OL materials contain carbon-based materials (including carbon black, carbon nanotubes, fullerenes and graphene), [4] organic dyes and polymers (such as phthalocyanine and porphyrin), [5,6] inorganic metal nanoparticle and quantum dots, [7][8][9] as well as organic and inorganic hybrid materials. [10][11][12][13][14][15][16] Hybrid materials possessing flexibility and possible synergic effects of diverse compo-nents are promising OL materials. As a result, aggregated crystalline materials like coordination polymers, metalorganic frameworks and metal complexes are among the materials that might become the next generation in the current field.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Benet from the development of chemical synthesis, many types of photosensitizers have been developed. Among them, noble metal complex photosensitizers have attracted great attention, such as ruthenium complexes, 25,26 platinum complexes, 27,28 iridium complexes, 29,30 etc. Iridium Ir(III) complexes possess higher intersystem crossing efficiency and better photobleaching resistance than some organic photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…This self-activated instantaneous response is a key advantage for practical applications. It has been widely demonstrated that OPL in the visible spectral range can be strongly enhanced if an excited-state absorption (ESA) phenomenon overlaps temporally and spectrally with the 2PA. ,, However, in spite of the rapid development since 2005 of two-photon dyes absorbing in the SWIR spectral range, OPL at 1300–1600 nm is a field of research still in its infancy. Therefore, only few reports describing OPL experiments at telecommunication wavelengths have appeared; so far, polymethine dyes, , functionalized porphyrins, and aza-BODIPY dyes in a solvent solution have been presented. , In all cases, a 2PA-induced ESA photophysical process is responsible for the OPL mechanism .…”
Section: Introductionmentioning
confidence: 99%